A general vector-based algorithm to generate weighted Voronoi diagrams based on ArcGIS Engine - Song, Tian; Cui, Ximin; Yu, Gong (International Conference on Industrial Mechatronics and Automation (Online), 2015)
The theoretical and computational aspects of weighted Voronoi diagrams have been widely researched and applied, but few algorithms are implemented in combination with the geographic information system software for practical use. A general vector-based approach is proposed to generate multiplicatively weighted Voronoi diagrams, additively weighted Voronoi diagrams and additively weighted power Voronoi diagrams for points by using methods of region division and region union based on ArcGIS Engine, aiming to establish a kind of spatial data model used for boundary division, urban centricity expression and force field analysis, etc. Finally, this paper shows an experiment proving the practicability of the proposed algorithm in the visualization of spatial data.